Mplementation of the Import Ban of Used Clothes Based on Law Number 7 of 2014 Concerning Trade in Respect of Law Number 8 of 1999 Concerning Consumer Protection in the Tolitoli District - Warda Said (MultiTech Publisher, 2023)
The purpose of writing this thesis is to find out the application of government regulations regarding the ban on the import of used clothing and legal protection for consumers of used clothing in Tolitoli district.The problem in implementing the ban on used clothing imports is about how the ban on used clothing imports is implemented based on trade laws and consumer protection laws in Tolitoli district? and how about legal protection for consumers in buying and selling used clothes in Tolitoli district?In writing this thesis, the author uses the research method of empirical juridical writing methods. The empirical juridical method in this study directed researchers to use primary data and legal prevention as patterns and behavior, where the location is intended to obtain information, explanations and data about the implementation of the ban on the import of used clothing in Tolitoli district.